Trust, trustworthiness, and traditional Islamic education - Asadullah, M.N. (Taylor & Francis, 2016)
This paper examines traditional Islamic school (i.e. madrasah) attendance as a determinant of social attitudes among secondary-schooled adolescents in rural Bangladesh. Although both recognized and traditional madrasah-enrolled adolescents show greater support for charity, we find no evidence that traditional madrasah attendance promotes “trust in others”. Attendance at recognized madrasahs, which use a state-approved curriculum, however, significantly increases social trust. The madrasah–trust connection is not explained by the role of teachers’ attitudes towards trust or professional background. Nor do we find evidence that the absence of an effect of traditional madrasah attendance on social trust is driven by their geographic locations. Given the differences between the two groups in terms of stated social preferences, our analysis warns against the practice of lumping state-recognized madrasahs and traditional madrasahs into one category.